PESAN DAKWAH DALAM UPACARA ADAT ANTAMA SAUKANG DESA BAROANGING KECAMATAN BANGKALA BARAT KABUPATEN JENEPONTO (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research raises the subject matter of How "Message of Da'wah in the Antama Saukang Beroanging traditional ceremony, West Bangkala District, Jeneponto Regency". Sub-problems, namely: 1. What is the form of the Da'wah message in the Antama Saukang Beroanging traditional ceremony, West Bangkala District, Jeneponto Regency? 2. What are the supporting and inhibiting factors for the message of da'wah in the traditional ceremony of Antama Saukang, Beroanging Village, West Bangkala District, and Jeneponto Regency? This study uses a descriptive qualitative research type located in Beroanging Village, West Bangkala District, Jeneponto Regency. The research approach used is. Source of data with purposive sampling technique which is considered to know about something that is expected by the researcher. The samples used as data sources in the study are traditional stakeholders, community leaders, organizers, traditional leaders, government, and other data sources that can be used as complementary data. Data collection methods are observation, in-depth interviews, and documentation. camera, recorder, notebook, and pen. The data processing and analysis technique was carried out in four stages, namely data reduction, data presentation, comparative analysis, and drawing conclusions.The results of this study indicate that the message of Da'wah in the traditional ceremony of Antama Saukang Beroanging, West Bangkala District, Jeneponto Regency, namely: creed messages, shari'a messages, and moral messages. The supporting and inhibiting factors for the message of da'wah in the traditional ceremony of Antama Saukang Beroanging, West Bangkala District, Jeneponto Regency, namely: the supporting factor is the support from religious leaders, community leaders, youth leaders, and support from the community, while the inhibiting factor is the existence of ideological barriers, The majority of the Muslim community for the Antama Saukang Beroanging traditional ceremony, West Bangkala District, Jeneponto Regency and many consider it a polytheistic tradition without understanding the Antama Saukang tradition in depth.